Hyperglycemia disturbs trophoblast functions and subsequently leads to failure of uterine spiral artery remodeling - Zhu, Yueyue; Liu, Xiaorui; Xu, Yichi; Lin, Yi (Frontiers in Endocrinology, 2023)
Uterine spiral artery remodeling is necessary for fetal growth and development as well as pregnancy outcomes. During remodeling, trophoblasts invade the arterial, replace the endothelium and disrupt the vascular smooth muscle, and are strictly regulated by the local microenvironment. Elevated glucose levels at the fetal-maternal interface are associated with disorganized placental villi and poor placental blood flow. Hyperglycemia disturbs trophoblasts proliferation and invasion via inhibiting the epithelial-mesenchymal transition, altering the protein expression of related proteases (MMP9, MMP2, and uPA) and angiogenic factors (VEGF, PIGF). Besides, hyperglycemia influences the cellular crosstalk between immune cells, trophoblast, and vascular cells, leading to the failure of spiral artery remodeling. This review provides insight into molecular mechanisms and signaling pathways of hyperglycemia that influence trophoblast functions and uterine spiral artery remodeling.